Overestimation of the Subjective Experience of Time in Social Anxiety: Effects of Facial Expression, Gaze Direction, and Time Course - Ishikawa, Kenta; Okubo, Matia (Frontiers in Psychology, 2016)
It is known that threatening stimuli increase emotional arousal, resulting in overestimating the subjective experience of passing time. Moreover, facial expressions and gaze direction interact to create socially threatening situations in people with social anxiety. The present study investigated the effect of social anxiety on the perceived duration of observing emotional faces with a direct or an averted gaze. Participants were divided into high, medium and low social anxiety groups based on social anxiety inventory scores. Participants then performed a temporal bisection task. Participants with high social anxiety provided larger overestimates for neutral faces with an averted gaze than those with low social anxiety in the second half of the task, whereas these differences were not found for angry face with direct and averted gaze. These results suggest that people with social anxiety perceive the duration of threatening situations as being longer than true durations based on objectively measured time.